2016
DOI: 10.4081/ijfs.2016.6055
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of perfluorooctane sulfonate and perfluorooctanoic acid exposure through fish consumption in Italy

Abstract: Perfluoroalkyl and polyfluoroalkyl substances (PFASs) are pollutants of anthropic origin with possible side effects on human health. Diet, and in particular fish and seafood, is considered the major intake pathway for humans. The present study investigated the levels of perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) contamination in twenty-five samples of fresh fillet of five widely consumed fish species purchased from large retailers in Italy, to be used for an estimation of the Italian po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…Previous studies in the US and other countries have investigated PFAS concentrations in fish purchased at local markets. In the US, PFAS were detected in 21 finfish and shellfish samples with the highest concentrations in fish from the Great Lakes region and in the Netherlands, PFOS was found in tilapia from Ecuador (∼200 ng/kg), shrimp from the Netherlands (∼550 ng/kg), and trout from Turkey (∼425 ng/kg). , In Italy, PFOS was found in 5 highly consumed fish ranging in concentration from 91 to 1896 ng/kg . Additionally, studies in the Czech Republic on canned fish thought to be from the Baltic Sea found PFOS concentrations ranging from 215 to 5401 ng/kg in mackerel, sardine, and cod liver …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in the US and other countries have investigated PFAS concentrations in fish purchased at local markets. In the US, PFAS were detected in 21 finfish and shellfish samples with the highest concentrations in fish from the Great Lakes region and in the Netherlands, PFOS was found in tilapia from Ecuador (∼200 ng/kg), shrimp from the Netherlands (∼550 ng/kg), and trout from Turkey (∼425 ng/kg). , In Italy, PFOS was found in 5 highly consumed fish ranging in concentration from 91 to 1896 ng/kg . Additionally, studies in the Czech Republic on canned fish thought to be from the Baltic Sea found PFOS concentrations ranging from 215 to 5401 ng/kg in mackerel, sardine, and cod liver …”
Section: Resultsmentioning
confidence: 99%
“…46,47 In Italy, PFOS was found in 5 highly consumed fish ranging in concentration from 91 to 1896 ng/kg. 48 Additionally, studies in the Czech Republic on canned fish thought to be from the Baltic Sea found PFOS concentrations ranging from 215 to 5401 ng/kg in mackerel, sardine, and cod liver. 49 Results from the Canadian Total Diet study found that meats contributed to around 90% of the total dietary intake of PFCAs and PFOS, and 2.7 μg/kg of PFOS was found in beef steak and 2.1 μg/kg in ground beef.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The levels of PFAS in wild sea bass Dicentrarchus labrax were higher (PFOS: 112-12,405 ng/kg; PFOA: 9-487 ng/kg) than those farmed. Interestingly, among farmed sea bass species, intensively farmed fishes showed lower PFAS values (PFOS: 11-105 ng/kg; PFOA: 9-51 ng/kg) compared to those extensively farmed [56].…”
Section: Biomonitoring Pfas In Aquatic Faunamentioning
confidence: 95%
“…For instance, a very recent study based in Tanzania has reported a PFAS contamination level in fish and seafood that would expose humans up to a threefold amount of perfluorooctanesulfonic acid (PFOS), with respect to the tolerable dose, under the regular fish consumption regimen of 0.016-0.027 kg/capita/day [55]. A similar study, taking into account the contamination of flathead mullet (Mugil cephalus), Atlantic mackerel (Scomber scombrus), and European plaice (Pleuronectes Platessa), hake (Merluccius merluccius), and sea bass (Dicentrarchus labrax), has reported PFAS contamination levels that were above the tolerable daily intake for toddlers' diet in Italy [56]. In this context, despite the Organization for Economic Cooperation and Development (OECD) has identified more than 4500 PFAS-related substances [57], only a few of them (<20) are regularly analysed and monitored, thus underestimating the real exposure to PFAS.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation